Workshop on Utilizing AI-Based Natural Language Processing (NLP) for Language Error Pattern Analysis and Improving the Quality of Students' Academic Writing - Nurwahidah, Lina Siti; Sela, Ai; Ambarwati, Ambarwati; Lestari, Anggia Septin Dwi; Nisa, Annida Firdaus; Aulia, Azka; Kurniawan, Erik (Fakultas Kewirausahaan Universitas Garut, 2025)
The use of AI-based tools in learning has been demonstrated by numerous studies, demonstrating that this technology can improve students' writing skills. This training is designed to provide a comprehensive understanding of the technical and theoretical aspects of using NLP technology in the context of language education. The application of NLP tools helps students identify and correct common language errors in academic writing, such as grammatical and spelling errors. Participants conducted text analysis of academic texts they had written before and after the training. Using NLP tools, they were able to identify errors and areas for improvement. The analysis results showed a significant reduction in error frequency after applying the techniques taught during the workshop. This training has positively contributed to students' academic writing skills, providing them with new skills and increasing their motivation to learn.